Polyketide synthesis in tobacco plants transformed with a plumbago zeylanica type III hexaketide synthase - Jadhav, Supriya; Phapale, Prasad; Thulasiram, Hirekodathakallu V.; Bhargava, Sujata (Phytochemistry, 2014)
A type III polyketide synthase from Plumbago zeylanica (PzPKS) was cloned and expressed in tobacco plants to study whether the transgenic tobacco plants expressing PzPKS synthesize the pharmacologically important polyketide, plumbagin. High resolution mass spectrometry based metabolite profiling of two transgenic events and wild type tobacco plants was carried out to investigate changes in polyketides, including plumbagin. Ten polyketides, which included six pyrones and four naphthalene derivatives, were identified in PzPKS transgenic plants. While one pyrone, styry1-2-pyranone, was detected in both, wild type and transgenic tobacco plants, three pyrones were expressed only in the leaves of transgenic tobacco plants. The transgenic tobacco plants did not accumulate plumbagin, but showed accumulation of isoshinanolone in the roots, which is postulated to be the reduction product of plumbagin. In addition, leaves of transgenic tobacco plants accumulated 3-methyl-1,8-naphthalenediol, a postulated precursor of plumbagin. The results indicated the requirement of additional Plumbago-specific components in the biosynthetic pathway of this polyketide. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: HR-MS; Metabolite profiling; Napthalene derivatives; Plumbago zeylanica L.; Polyketide synthase; Pyrones; Tobacco transgenics

Integrative analysis of rewired central metabolism in temozolomide resistant cells - Immanuel, Selva Rupa C.; Ghanate, Avinash D.; Parmar, Dharmeshkumar S.; Marriage, Fiona; Panchagnula, Venkateswarlu; Day, Nap J.; Raghunathan, Anu (Biochemical and Biophysical Research Communications, 2018)
An authenticated U87MG clonal glioblastoma cell line was investigated to identify a sub-population of neurospheroidal (NSP) cells within the main epithelial population (U87MG). The NSP cells sorted using Fluorescence Assisted Cell Sorting (FACS) showed varied morphology, 30% lower growth rates, 40% higher IC50 values for temozolomide drug and could differentiate into the glial cell type (NDx). Metabolite profiling using HR-LCMS identified glucose, glutamine and serine in both populations and tryptophan only in U87MG as growth limiting substrates. Glycine, alanine, glutamate and proline were secreted by U87MG, however proline and glycine were re-utilized in NSP. Exo-metabolite profiling and phenotypic microarrays identified differential metabolism of primary carbon sources glucose and derived pyruvate for U87MG; glutamine and derived glutamate metabolism in NSP. Differential mRNA abundance of AKT1, PTEN, PIK3CA controlling metabolism, drug efflux, nutrient transport and epigenetic control MDM2 are potentially critical in shaping DNA methylation effects of temozolomide. Our study provides a new insight into the combined effect of these factors leading to temozolomide resistance in NSP. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Glutamine; Metabolic rewiring; Metabolite profiling; mRNA abundances; Temozolomide resistance; U87MG

Terpene profiling, transcriptome analysis and characterization of cis–terpineol synthase from Ocimum - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Dholakia, Bhushan B.; Lavhale, Santosh G.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Physiology and Molecular Biology of Plants, 2019)
Ocimum species produces a varied mix of different metabolites that imparts immense medicinal properties. To explore this chemo-diversity, we initially carried out metabolite profiling of different tissues of five Ocimum species and identified the major terpenes. This analysis broadly classified these five Ocimum species into two distinct chemotypes namely, phenylpropanoid-rich and terpene-rich. In particular, -caryophyllene, myrcene, limonene, camphor, borneol and selinene were major terpenes present in these Ocimum species. Subsequently, transcriptomic analysis of pooled RNA samples from different tissues of Ocimum gratissimum, O. tenuiflorum and O. kilimandscharicum identified 38 unique transcripts of terpene synthase (TPS) gene family. Full-length gene cloning, followed by sequencing and phylogenetic analysis of three TPS transcripts were carried out along with their expression in various tissues. Terpenoid metabolite and expression profiling of candidate TPS genes in various tissues of Ocimum species revealed spatial variances. Further, putative TPS contig 19414 (TPS1) was selected to corroborate its role in terpene biosynthesis. Agrobacterium-mediated transient over-expression assay of TPS1 in the leaves of O. kilimandscharicum and subsequent metabolic and gene expression analyses indicated it as a cis–terpineol synthase. Overall, present study provided deeper understanding of terpene diversity in Ocimum species and might help in the enhancement of their terpene content through advanced biotechnological approaches.
Keywords: Agro-infiltration assay; Metabolite profiling; Ocimum; Terpene synthase; Terpenes; Transcriptome

Targeted metabolite profiling and de novo transcriptome sequencing reveal the key terpene synthase genes in medicinally important plant, Couroupita guianensis Aubl - Thulasiram, Hirekodathakallu V.; Karegaonkar, Shrikant Jagannathrao; Sharma, Poojadevi; Kumar, Ashish; Ramkumar, Sudha; Pandreka, Avinash (Plant Genetic Resources-Characterization and Utilization, 2023)
The Lecythidaceae family tree, Couroupita guianensis Aubl, popularly known as Nagpushpa, is a widely cultivated ornamental tree with several uses in traditional medicine. The tree is revered as highly sacred in Indian traditional culture due to its uniquely shaped, fragrant flowers. Considering the significance, we were prompted to carry out the metabolite and transcriptome analysis of Nagapushpa. The flower, petals, stamen, stem and leaf of C. guianensis were metabolically profiled, and it was discovered that the flower tissue contained the highest terpenoid reservoir. A number of terpenoid pathway transcripts were also found in the flower tissue after transcriptome profiling. KEGG pathway mapping was carried out to correlate transcript sequences with the biosynthesis of different types of terpenes. We were able to clone three full-length terpene synthase gene candidates, i.e. monoterpene ocimene synthase, diterpene ent-kaurene synthase and sesquiterpene farnesene synthase. The transcript expression of selected terpene synthase genes was also verified in flower tissue. These cloned sequences were used for in silico structural investigations and protein function prediction at the level of 3D structure. The data presented in this study provide a comprehensive resource for the metabolic and transcriptomic profiles of C. guianensis. The study paves the way towards the elucidation of terpene biosynthetic pathway in C. guianensis and heterologous production of useful terpenoids in the future.
Keywords: Couroupita guianensis Aubl; flower; Metabolite profiling; terpene synthases; Transcriptomics

Comprehensive tissue specific analysis of antioxidant potential and metabolite profiling of a vulnerable therapeutic herb Ceropegia sahyadrica - Pandey, Meena; Dholakia, Bhushan B.; Saraf, Purva S.; Punekar, Sachin A.; Giri, Ashok P. (3 Biotech, 2025)
This study investigated tissue-culture of an endangered medicinal herb, Ceropegia sahyadrica, along with tissue-specific variation in antioxidant activity and GC-MS based phytochemical profiling using wild and in vitro explants. In vitro leaf explants exhibited callus induction rate of 100% in Murashige and Skoog media containing 6-benzylaminopurine (4 mu M) and 2,4-dichlorophenoxyacetic acid (2 mu M) with 5% sucrose, whereas in vitro root explant achieved 66.7% with the combination of 2 mu M 6-benzylaminopurine and 1 mu M 2,4-dichlorophenoxyacetic acid in Murashige and Skoog medium. Microtuberization was most pronounced in in vitro root explants with a maximum response of 73.3% in 1 mu M indole-3-acetic acid, 2 mu M 6-benzylaminopurine and 5% sucrose. Scanning electron microscopy imaging revealed distinct cellular organization among tissues. Further, antioxidant potential assessed through 1,1-diphenyl-2-picrylhydrazyl radical scavenging assays and estimated total phenolic content showed metabolic variation and commonality between in vitro and wild tissues. Additionally, phytochemical profiling by gas chromatography-mass spectrometry identified 201 compounds, including alkaloids, fatty acid methyl esters, flavonoids, phytosterols and other bioactive molecules with alterations in metabolite profiles between in vitro and wild tissues. These findings demonstrated that explant origin and culture condition might significantly influence metabolic responses for conservation and ensures a reliable source of bioactive compound.
Keywords: Ceropegia- Conservation; Endemic medicinal herb; GC-MS; Metabolite profiling; Tuberization

Metabolomic profiling unravels the role of sphingolipid pathways in spot blotch resistance in wheat - Yadav, Sagar; Maiti, Saborni; Mundhe, Swapnil; Kadoo, Narendra (Acta Physiologiae Plantarum, 2025)
Spot blotch, caused by the soil- and air-borne fungal pathogen Bipolaris sorokiniana, is a major threat to wheat production. The disease is reaching epidemic proportions in wheat-growing areas, particularly in South Asia, South America, Africa, and Australia. In India, over 25 million hectares of wheat-growing area is threatened by this disease. A systematic study of metabolites can provide insights into the molecular basis of this disease. In the present study, we evaluated the impact of B. sorokiniana inoculation on two wheat varieties, Chirya3 (resistant to spot blotch) and DDK1025 (susceptible to spot blotch). We performed time-course non-targeted metabolite profiling of the pathogen-inoculated and mock-inoculated plants using liquid chromatography coupled with high-resolution mass spectrometry (LC-HRMS). Multivariate analysis was performed to construct a comprehensive statistical workflow, which led to the defined ``metabolomic phenotypes''. Modeling by Orthogonal Projection to Latent Structures-Discriminant Analysis (OPLS-DA) revealed significant metabolites in responses of the resistant and susceptible varieties to pathogen inoculation. A total of 699 metabolites displayed significant variations during the progression of infection. B. sorokiniana-inoculated Chirya3 exhibited high levels of some metabolites, such as sphingolipids, cysteine, phenylalanine, shikimates, etc. The study revealed that sphingolipid pathways are critical in resistance mechanisms contributing to enhanced lignification and disease resistance in wheat.
Keywords: Cochliobolus sativus; High-resolution mass spectrometry; LC-HRMS; Metabolite profiling; OPLS-DA; plant-pathogen interaction